HOTSCC-Ichsan: HOTS of Climate Change with Ichsan’s Taxonomy for Elementary Teacher Candidates - Ilmi Zajuli Ichsan; Diana Vivanti Sigit; Nur Fadli Hazhar Fachrial; Sri Nurafifah; Ahmad Ali; Maricar H. Sison; Nurfadhilah Nurfadhilah; Yusi Rahmaniar; Rika Sa’diyah (Postgraduate, University of Mataram, 2022)
It is a necessity to develop environmental learning to solve climate change problems, in particular. One of the focuses is climate change learning at the elementary school level that requires elementary teacher candidates to understand various climate change issues. Skills needed are Higher Order Thinking Skills (HOTS) measurable using Ichsan’s taxonomy as an innovation. Ichsan’s taxonomy consists of six thinking levels, namely identify, compare, implement, criticize problems, solve problems, and develop innovation. The study describes the HOTS of elementary teacher candidates using the HOTS of Climate Change with Ichsan’s taxonomy (HOTSCC-Ichsan). The study uses a descriptive method with a survey as the data collection technique. The study finds that the HOTS scores of the elementary teacher candidates measured using the HOTSCC-Ichsan are in a very low category (28.03). The finding indicates the need to enhance the HOTS-based learning intensively for the elementary teacher candidates. It requires learning media development to address the low HOTS. The research conclusion is that the HOTS of the elementary teacher candidates is low and needs an improvement